Provenance of the Paleozoic to Mesozoic Siliciclastic Rocks of the Istanbul Zone Constrains the Timing of the Rheic Ocean Closure in the Eastern Mediterranean Region. Issue 12 (13th December 2021) - Akdoğan, Remziye; Hu, Xiumian; Okay, Aral I.; Topuz, Gültekin; Xue, Weiwei
Abstract: The Intra‐Pontide Suture between the Istanbul and Sakarya zones was regarded debatably either as a Neotethyan Suture or a trace of the Rheic Suture in Turkey. Here, we present U‐Pb ages and Lu‐Hf isotopic compositions of detrital zircons from the Silurian to Triassic sandstones of the Istanbul Zone. Upper Silurian‐Lower Devonian sandstone is dominated by Mesoproterozoic zircons (1950–900 Ma), with subordinate peaks at the latest Neoproterozoic to Silurian (750–420 Ma) and mid‐Archean (2850–2750 Ma) confirming their Avalonian affinity. Detrital zircon ages from Carboniferous‐Triassic sandstones show major peaks at Carboniferous‐Early Permian (360–270 Ma) and Late Neoproterozoic–Cambrian (750–480 Ma) while Mesoproterozoic zircons are insignificant. The εHf(t) values of the detrital zircons exhibit a wide range from −21.3 to +11.7, and over 62% of zircon grains have negative values, largely coinciding with those of the Paleozoic igneous rocks in the Sakarya Zone. The Istanbul Zone is devoid of Carboniferous igneous and/or metamorphic rocks. Therefore, abundant Carboniferous zircons and the disappearance of the Mesoproterozoic zircons in the Carboniferous‐Triassic sandstones of the Istanbul Zone require juxtaposition with a continental domain similar to the Sakarya and Strandja zones, which are characterized by widespread Carboniferous magmatism. We suggest that the Intra‐Pontide Suture represents the trace of the Rheic Suture in Turkey, along which Avalonia and Armorica collided during the Early Carboniferous. Key Points: U‐Pb zircon ages in the Carboniferous to Triassic sandstones of the Istanbul Zone are mainly Carboniferous and Late Neoproterozoic–Cambrian The Istanbul Zone lacks Carboniferous igneous/metamorphic events, while they are characteristics of the Armorican Sakarya and Strandja zones The contact between the Avalonian Istanbul Zone and Armorican Sakarya Zone represents the eastward continuation of the Rheic Suture